Synthesis and photophysical properties of novel oxadiazole substituted BODIPY fluorophores. (7th March 2022) - Matveeva, Maria D.; Zhilyaev, Dmitry I.; Miftyakhova, Almira R.; Chulkin, Pavel; Janasik, Patryk; Voskressensky, Leonid G.; Talarico, Giovanni; Efimov, Ilya V.
Abstract : Using 3-phenyl-5-(5-phenyl-1 H -pyrrol-3-yl)-1, 2, 4-oxadiazole, BODIPYs with the oxadiazole groups at the 1, 7-positions were prepared and their photophysical properties were characterized. Abstract : Using 3-phenyl-5-(5-phenyl-1 H -pyrrol-3-yl)-1, 2, 4-oxadiazole, BODIPYs with the oxadiazole groups at the 1, 7-positions were prepared and their photophysical properties were characterized. The method employs 2, 4-diphenyl substituted pyrrole and various aromatic aldehydes under solvent-free conditions. Due to the attachment of the oxadiazole groups at the 1, 7-positions, the BODIPYs show long-wavelength absorption and emission in the near-infrared region.